PENGARUH LABA (RUGI) BERSIH DAN ARUS KAS BERSIH TERHADAP RETURN SAHAM PADA PERUSAHAAN MAN UFAKT UR AUTOMOTIVE AND ALLIED PRODUCTS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitanggang, Abdonsius (UNIKA Santo Thomas, 2011)
In manufacturing companies Automotive and Allied Products listed on the Indonesia Stock Exchange in 2006-2007 showed fluctuations of income (loss), net cash ï¬‚ows and stock returns and the consequences of the rise and fall of income (loss) and cash flows cause stock returns ï¬‚uctuate too . So the problem is formulated